Possible-World dan Pelanggaran-Batas Antardunia dalam Novel Kappa Karya Ryunosuke Akutagawa - Hangganararas, Hatindriya; Rabbani, Ilham (J-Litera: Jurnal Kajian Bahasa, Sastra dan Budaya Jepang, 2022)
The Kappa by Ryunosuke Akutagawa tells about the life of the kappa, a mythological creature that met "I" on his climbing journey. "I" character stumbled, then found himself already in the kappa world. This research will answer: first, how is the reflection of the real world and the possible-world in Kappa's novel?; second, how many of the rules that describe one world are broken by the other? This research used Marie-Laure Ryan's narrative or possible-world concept as the main theory. The method used in this research is descriptive-qualitative. This research concluded two things: first, in the Kappa novel, the dominant condition of the kappa world is described as a possible-world that has an advanced culture, which is pretty similar to what Japan experienced in the 1920s in the real world; and second, the rules that each species breaks (humans and kappa), from the real world to the kappa world, are not explained in detail, except for the part when the "I "is about to return to the human world. Unfortunately, the explanation is still not detailed because it is a transition chapter (from "Part XVI" to "Part XVII"). Also, at the opening of the narration "Part XVII", the narrator has lived an ordinary life (before experiencing symptoms of madness) in the human world. These broken rules happen at the beginning and end of the novel, which means framing the events of the "I "long experience in the kappa world, where he finds a world that is no less vast than the world that humans live inside.